The Effectiveness of Betel Leaf (Piper betle) Decoction in the Management of Pruritus among Elderly Residents of a Social Welfare Institution in Banyuwangi, 2025 - Akhmad Yanuar Fahmi Pamungkas (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: Itching in the elderly is a common complaint in skin diseases and is usually chronic, meaning that this condition lasts for a long time. Betel leaf decoction is useful for relieving pruritus (itchy skin) because it contains active compounds such as eugenol, tannins, and flavonoids which are anti-inflammatory, antimicrobial, and antiseptic. This study aims to determine the effect of giving betel leaf decoction on the sensation of itching in the elderly with pruritus at the UPT Panti Sosial Tresna Werdha Banyuwangi in 2025 Methods: This study used a pre-experimental pre-test post-test without control research design with purposive sampling technique. The total sample was 19 respondents who met the inclusion criteria. Data were obtained from the PSS questionnaire. Data analysis techniques after data normality testing were carried out using the Wilcoxon test Results: Based on the results of the research that has been done, the results of the Data Analysis test with the Wilcoxon match pairs test using SPSS 16 for windows obtained the results of Asymp Sig. (2-tailed) p value = 0.001 <0.05 which means H0 is rejected Ha is accepted which means there is a significant effect between the provision of warm compresses of boiled betel leaves on the sensation of itching in the elderly with pruritus at the UPT Panti Sosial Tresna Werdha Banyuwangi in 2025 Conclusions: Warm compress therapy with boiled betel leaves can reduce the sensation of itching in the elderly. This method is very effective to be applied as a preventive measure in an effort to reduce itching in the elderly.